The implications of pricing on social learning. Issue 4 (25th November 2022) - Arieli, Itai; Koren, Moran; Smorodinsky, Rann
Abstract : Two firms produce substitute goods of unknown quality. At each stage the firms set prices and a consumer with private information and unit demand buys from one of the firms. Both firms and consumers see the entire history of prices and purchases. Will such markets aggregate information? Will the firm with the superior product necessarily prevail? We adapt the classic social‐learning model by introducing strategic dynamic pricing. We provide necessary and sufficient conditions for asymptotic learning. In contrast to previous results, we show that asymptotic learning can occur when signals are bounded, namely, happens when the density of the consumers at the boundaries of the posterior belief distribution goes to zero. We refer to this property of the signal structure as the "vanishing margins" property.